Effects of dual-task interventions on gait performance of patients with parkinson’s disease: a systematic review - Santos, Luís A. A. (2016)
OBJECTIVE: Parkinson’s disease is characterized by motor and non-motor symptoms that impair patients’ gait performance, especially while performing dual/concurrent tasks. These deficits impair patients’ daily function, because dual-tasking is a crucial ability in terms of everyday living. The aim of this study was to systematically review the effects of dual task interventions on gait performance of patients with Parkinson’s disease. METHOD: Studies were retrieved from MEDLINE/PubMed, LILACS and SciELO. We used the PICOS strategy to determine eligibility criteria. The search strategy included an advanced search on the included databases, using the following search query: “Parkinson’s Disease” AND “Double Task” OR “Concurrent Tasks” OR “Gait” AND “Walk”. Study selection was carried out by two independent researchers and a third one was called when consensus was needed. RESULTS: A total of 188 articles were identified: 169 articles from Medline/PubMed, 10 articles in SciELO, 8 articles in LILACS and 1 item from manual searches. A total of 56 articles were analyzed regarding the eligibility and exclusion criteria based on full text. A final total of 7 studies were included in the systematic review. CONCLUSION: The different types of dual-task interventions reported (dance, sound stimuli, visual and somatosensory) were associated to improvements in several gait performance indicators of Parkinson’s disease patients, including gait speed, stride time and length, cadence and step length. External stimuli seem to play a critical role on specific training effects on dual-task gait performance.